Analisis Perencanaan Obat di UPTD Farmasi Dinas Kesehatan Kota Depok - Fortunandha, Dhea Keyle; Intiasari, Arih Diyaning; Kurniawan, Arif (Asosiasi Institusi Pendidikan Tinggi Kesehatan Masyarakat Indonesia, 2021)
Background: Planning is an initial stage and as an important and decisive stage, because planning for drug needs will affect the next cycle of drug management in the health care unit. If the planning are weak, it will give a negative impact on the overall management cycle. The findings of expired drugs is a negative impact experienced by the Pharmaceutical Technical Service Unit of Government Health Department in Depok, so it can be assumed that drug planning has not been carried out properly. Methods: This research is a qualitative research with a case study design. This research was conducted at the Pharmaceutical Technical Service Unit of Government Health Department in Depok with 8 informants. The data analysis used was content analysis. Results: Analysis of drug planning at the Pharmaceutical Technical Service Unit of Government Health Department in Depok shows that limited human resources do not yet know enough about the process of calculating drug needs, recording and reporting drug logistics which is done manually to be the main obstacle in using data for drug planning, selecting types of drugs and calculating drug needs not completely according to the guidelines. Drug planning is not done optimally because there are expired drugs and drug stock vacancies which cause the planning results are not as expected. So it is necessary to monitor and evaluate the availability of drugs so that the findings of expired drugs can be minimized as well as training in drug management so that drug managers understand about good drug management and methods of planning drug needs in accordance with established guidelines. Conclusion: Drug planning carried out by the Pharmaceutical Technical Service Unit of Government Health Department in Depok is not fully in accordance with the technical guidelines for drug procurement also there are expired drugs and drug stock vacancies which cause the planning results are not as expected. The existence of expired drugs and drug stock vacancies at the UPTD Pharmacy at the Depok City Health Service are caused by factors outside the system, including short drug expiration periods, changes in disease patterns, COVID-19 pandemic conditions that hinder the distribution of program drugs to program targets, and drugs not available at e-catalog.